113Cd NMR Studies of Reconstituted Seven-Cadmium Metallothionein: Evidence for Structural Flexibility - Vasak,M; Hawkes,GE; Nicholson,JK; Sadler,PJ (Biochemistry, 1985)
A reproducible method for the reconstitution of rabbit liver metallothionein (MT) containing seven cadmium atoms per mole of protein is described. This protein was studied in detail by 113Cd NMR at 88-, 55-, and 44-MHz frequencies, including the effects of pH, temperature, and ionic strength on the spectra. Our results differ significantly from previous reports of 113Cd NMR on similar samples. Thus, the spectra of both chromatographically distinguishable isoforms MT1 and MT2 were not identical, and neither could be interpreted in terms of a unique static model with the seven Cd ions forming two independent clusters of four and three Cd ions. Large differential shifts of 113Cd resonances were observed with changes in temperature over the range 277-320 K and ionic strength (0.02-0.5 M). At low temperature a slow structural change (half-life of several minutes) was detected. The structure was more rigid at high ionic strength. The frequency dependence and two-dimensional J-resolved spectra revealed that 113Cd resonances were composed of several overlapping peaks, complicating the interpretation of fine structure in one-dimensional spectra. A new flexible model of the Cd cluster in metallothionein is proposed. This model incorporates dynamic thiolate exchange reactions and involves several configurational substates of the protein. The possible relationship of such flexibility to the function of metallothionein is discussed. © 1985, American Chemical Society. All rights reserved.